ANALISIS STRATEGI PEMASARAN DALAM MENINGKATKAN PENJUALAN PADA CAFE OX COFFEE MEDAN - Yasotha, Yasotha; Lumbantungkup , Rani; Siregar , Muhliza; Indriati , Ayu; Azhari , Zahirah; Djeremy Busra , Aditya (Jurnal Multidisiplin Sosial dan Humaniora, 2024)
The development of the coffee business world is currently increasingly rapid, giving rise to very tight competition between coffee businesses. The purpose of this research is to find out whether the marketing strategy implemented by Cafe Ox Coffee Medan can increase the sales of the food and beverages it sells. This research uses a qualitative descriptive method by collecting data and information using interview-observation techniques with employees of Cafe OX Coffee Medan and the results of sales data reports for 3 consecutive months. The research results show that the marketing strategy implemented at OX Coffee Medan is effective, as shown by the increase in turnover every consecutive month.